Evidence from Indian studies on safety and efficacy of therapeutic transcranial magnetic stimulation across neuropsychiatric disorders- A systematic review and meta-analysis - Sai Krishna Tikka; Sangha Mitra Godi; M Aleem Siddiqui; Shobit Garg (Indian Journal of Psychiatry)
Repetitive transcranial magnetic stimulation (rTMS) is potentially effective as an augmentation strategy in the treatment of many neuropsychiatric conditions. Several Indian studies have been conducted in this regard. We aimed to quantitatively synthesize evidence from Indian studies assessing efficacy and safety of rTMS across broad range of neuropsychiatric conditions. Fifty two studies- both randomized controlled and non-controlled studies were included for a series of random-effects meta-analyses. Pre-post intervention effects of rTMS efficacy were estimated in “active only” rTMS treatment arms/groups and “active vs sham” (sham-controlled) studies using pooled Standardized Mean Differences (SMDs). The outcomes were ‘any depression’, depression in unipolar/bipolar depressive disorder, depression in obsessive compulsive disorder (OCD), depression in schizophrenia, schizophrenia symptoms (positive, negative, total psychopathology, auditory hallucinations and cognitive deficits), obsessive compulsive symptoms of OCD, mania, craving/compulsion in substance use disorders (SUDs) and migraine (headache severity and frequency). Frequencies and odds ratios (OR) for adverse events were calculated. Methodological quality of included studies, publication bias and sensitivity assessment for each meta-analyses was conducted. Meta-analyses of “active only” studies suggested a significant effect of rTMS for all outcomes, with moderate to large effect sizes, at both end of treatment as well as at follow-up. However, except for migraine (headache severity and frequency) with large effect sizes at end of treatment only and craving in alcohol dependence where moderate effect size at follow-up only, rTMS was not found to be effective for any outcome in the series of “active vs sham” meta-analyses. Significant heterogeneity was seen. Serious adverse events were rare. Publication bias was common and the sham controlled positive results lost significance in sensitivity analysis. We conclude that rTMS is safe and shows positive results in ‘only active’ treatment groups for all the studied neuropsychiatric conditions. However, the sham-controlled evidence for efficacy is negative from India. Conclusion rTMS is safe and shows positive results in “only active” treatment groups for all the studied neuropsychiatric conditions. However, the sham-controlled evidence for efficacy is negative from India.